Strategy for Developing Mount Gajah Tourism as a Tourism Destination in Getasan - Desi Lukuaka; Mia Elvina; Oskar Katanga Maudjawa; Sutarto Wijono (Journal of Social Research, 2023)
Coronavirus Disease or Covid-19 has swept the world and taken a lot of casualties and all human life has been paralyzed. In addition, the Covid-19 pandemic has also had an impact on the community's economy which caused a financial crisis due to the termination of work for employees, and businesses that had to be closed both in the culinary, fashion, and tourism fields. The tourism industry is one of the sources of national income that plays a role in improving the welfare of the local community. Mount Gajah is one of the new tourist attractions in Getasan – Central Java. Tourism development strategies are needed to maximize profits and reduce the problem of efforts to develop tourism destinations post-covid-19. This research was conducted to determine the strategies used in the development of elephant mountain tourism. The results showed that there are several strategies that can be applied to develop tourist areas, namely increasing the promotion of elephant mountain tourism, paying attention to accessibility, and elephant mountain areas as a support for tourism development in Getasan.